Pengaruh Program Bauran Pemasaran Jasa Tabungan terhadap Loyalitas Penabung pada PT Bank Mandiri Sudirman Bawah Cabang Pekanbaru - Mahyarni -; Astuti Meflinda (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research was conducted at PT Bank Mandiri Sudirman Bawah Pekanbaru Branch, with the aim of the study is to determine the level of customer satisfaction towards the marketing mix saving service program and to determine the influence of the program towards loyalty of the savers. The population in this study are all PT Bank Mandiri Sudirman Bawah customers, totaling 25 029 people, while sampling was done by purposive sampling method. Sample size was 100 respondents. Data analysis using Descriptive and Regression Analysis. Analysis result shows that marketing mix saving service program (product, price, place, promotion, people, physical evidence and processes) significantly affect the loyalty of savers. As for product (x1), price (x2), place (x3), promotion (x4), People (x5), Physical Evidence (x6) and processes (X7) each significantly influence loyalty savers. The most dominant variable influencing savers loyalty is the people.Keywords: Product, Price, Place, Promotion, People, Physical Evidence, processes and loyalty